S117. FAVORABLE LONG-TERM SAFETY PROFILE OF LUMATEPERONE IITI-007): RESULTS FROM A 12 MONTH OPEN LABEL SAFETY STUDY FOR LUMATEPERONE IN PATIENTS WITH STABLE SYMPTOMS OF SCHIZOPHRENIA. (9th April 2019) - Vanover, Kimberly; Satlin, Andrew; Durgam, Saresh; Weingart, Michal; Saillard, Jelena; Sanchez, Juan; Hossain, Shawon; Glass, Steven; Kozauer, Susan; Mates, Sharon; Davis, Robert
Abstract: Background: Lumateperone (ITI-007) is an investigational drug for the treatment of schizophrenia, bipolar depression, agitation associated with dementia and other neuropsychiatric disorders. With a unique mechanism of action, lumateperone modulates serotonin, dopamine and glutamate neurotransmission. More specifically, lumateperone is a potent serotonin 5-HT2A receptor antagonist, a dopamine D2 receptor pre-synaptic partial agonist and post-synaptic antagonist, a dopamine D1 receptor-dependent modulator of glutamate (both NDMA and AMPA), and a serotonin reuptake inhibitor. In two previous placebo-controlled trials, lumateperone demonstrated statistically significant improvements over placebo on change from baseline on the PANSS total score in patients with acute schizophrenia. In this population, lumateperone was found to be well tolerated with a safety profile similar to placebo. Moreover, the first part of an open-label safety study demonstrated a favorable safety profile, with improvement in metabolic parameters, when patients with stable schizophrenia were switched from standard-of-care (SOC) to lumateperone for 6-weeks of treatment. These safety benefits were lost when patients were switched back to SOC. The purpose of the present study, the second part of the open-label safety study, was to evaluate the long-term safety and tolerability of lumateperone administered to patients with stable schizophrenia for up to 1-year treatment duration. Methods: 603 patients with schizophrenia were treated for up to 1 year with lumateperone tosylate (ITI-007) 60 mg QPM, with no dose titration. To be eligible for inclusion in the study, patients must have had a clinical diagnosis of schizophrenia according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and be stable with respect to their schizophrenia symptoms. The primary objective was to determine the safety of lumateperone, assessed by adverse events, body weight, 12-lead electrocardiograms, vital signs, clinical laboratory tests, motor assessments, and the Columbia-Suicide Severity Rating Scale. The secondary objectives were to determine the effectiveness of lumateperone to maintain or improve psychopathology as measured by the PANSS and the CGI-S. Results: Lumateperone was well tolerated with a favorable safety profile. There were no clinically relevant changes in extrapyramidal side effect assessments. Mean body weight decreased from SOC antipsychotic baseline with long-term lumateperone treatment. Lumateperone also demonstrated a favorable cardiometabolic and endocrine safety profile. Symptoms of schizophrenia generally remained stable or improved as measured by PANSS and CGI-S. Discussion: Lumateperone represents a novel approach to the treatment of schizophrenia with a favorable safety profile in clinical trials. The lack of metabolic, motor and cardiovascular safety issues presents a safety profile differentiated from SOC antipsychotic therapy. These data, taken together, are consistent with and extend data previously reported in placebo-controlled studies in patients with acute schizophrenia with lumateperone and short-term evaluation of lumateperone's safety.